PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. BANK NEGARA INDONESIA DI SITUBONDO - Pratiwi, Sonya Dita; Karnadi, Karnadi; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
One of the important factors in the field of human resources is to create an Organizational Culture and motivation in the company which is the right of employees and the obligation of the company to support the contribution of workers in order to achieve predetermined goals. The purpose of this study is to analyze and test the influence of Organizational Culture on Employee Performance through Motivation as an Intervening Variable in PT. Bnak Negara Indonesia. The population in this study were permanent employees of PT. State Bank of Indonesia. The sampling method is determined by a saturated system. Data analysis and hypothesis testing in the study using structural equation model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, showed that Organizational Culture has a significant positive effect on Motivation, Organizational Culture has a positive but not significant effect on employee performance, Motivation has a significant positive effect on employee performance, Organizational Culture has a positive but insignificant effect on employee performance through motivation.